Early changes in the extracellular matrix of the degenerating intervertebral disc, assessed by Fourier transform infrared imaging. Issue 10 (October 2018) - Emanuel, K.S.; Mader, K.T.; Peeters, M.; Kingma, I.; Rustenburg, C.M.E.; Vergroesen, P.-P.A.; Sammon, C.; Smit, T.H.
Summary: Objective: Mechanical overloading induces a degenerative cell response in the intervertebral disc. However, early changes in the extracellular matrix (ECM) are challenging to assess with conventional techniques. Fourier Transform Infrared (FTIR) imaging allows visualization and quantification of the ECM. We aim to identify markers for disc degeneration and apply these to investigate early degenerative changes due to overloading and katabolic cell activity. Design: Three experiments were conducted; Exp 1.: In vivo, lumbar spines of seven goats were operated: one disc was injected with chondroitinase ABC [cABC (mild degeneration)] and compared to the adjacent disc (control) after 24 weeks. Exp 2a: Ex vivo, caprine discs received physiological loading ( n  = 10) or overloading ( n  = 10) in a bioreactor. Exp 2b: Cell activity was diminished prior to testing by freeze–thaw cycles, 18 discs were then tested as in Exp 2a. In all experiments, FTIR images (spectral region: 1000–1300 cm −1 ) of mid-sagittal slices were analyzed using multivariate curve resolution. Results: In vivo, FTIR was more sensitive than biochemical and histological analysis in identifying reduced proteoglycan content ( P  = 0.046) and increased collagen content in degenerated discs ( P  < 0.01). Notably, FTIR analysis additionally showed disorganization of the ECM, indicated by increased collagen entropy ( P  = 0.011). Ex vivo, the proteoglycan/collagen ratio decreased due to overloading ( P  = 0.047) and collagen entropy increased ( P  = 0.047). Cell activity affected collagen content only ( P  = 0.044). Conclusion: FTIR imaging allows a more detailed investigation of early disc degeneration than traditional measures. Changes due to mild overloading could be assessed and quantified. Matrix remodeling is the first detectable step towards intervertebral disc degeneration.